PENGARUH BERMAIN PUZZLE JAM TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK USIA 4-5 TAHUN DI PAUD BUNGA KIAMBANG KECAMATAN SAIL PEKANBARU - Zuraida, Zuraida; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine the ability to recognize the symbol of the number of children aged 4-5 years prior to the application of playing Puzzle hours in PAUD Bunga Kiambang Sail Pekanbaru, 2) To determine the ability to recognize the symbol of the number of children aged 4-5 years after the application of playing Puzzle hours in PAUD Bunga Kiambang Sail Pekanbaru, 3) To determine the effect of the application of playing Puzzle hours of the ability to know the symbol of the number of children aged 4-5 years in PAUD Bunga Kiambang Sail Pekanbaru. This type of research used in this research is the experimental approach a study that sought influence of certain variables on other variables in strictly controlled conditions. The research sample is graders B consisting of 15 people, 7 boys and 8 girls. Collecting data using observation and documentation. Based on the survey results revealed that 1) The ability to recognize ability emblem number of children aged 4-5 years in PAUD Bunga Kiambang Sail Pekanbaru before treatment is given in the form of playing Puzzle hours is low, 2) The ability to recognize ability emblem number of children aged 4-5 years in PAUD Bunga Kiambang Sail Pekanbaru after treatment is given in the form of playing Puzzle hours have increased and relatively high, 3) Play Puzzle hours have a significant impact on the ability of the symbol of the ability to know the number of children aged 4-5 years in PAUD Bunga Kiambang Sail Pekanbaru. It can be seen that there are differences related to increase the child's ability to recognize the emblem of numbers before and after treatment, 4) Play Puzzle hours have amounted to 37.78% influence on the ability of the symbol of the ability to know the number of children aged 4-5 years in PAUD Bunga Kiambang Sail Pekanbaru.Keywords: Play Puzzle hours, Symbol Numbers